Flow measurement engineering handbook - Miller, R.W. (Richard W.) (McGraw Hill, 1989)
Single-source handbook to the selection, design, specification, and installation of flowmeters measuring liquid, gas, and steam flows. Miller (president, RW Miller Consulting) supplies the key information on seven-place equation constants and simplifying equations and includes many examples, graphs, and tables to help improve performance, and save time and expense. The revised edition features the latest ISO, ASME, and ANSI-related standards, meter influence quantities for flowmeters, and proposed orifice and nozzle equations. The nine appendices present discussions and proofs, and the generalized properties of liquids and gas. Provides definitive information on selecting, sizing, and performing pipe-flow-rate calculations, using the latest ISO and ANSI standards in both SI and US equivalents. Also presents physical property data, support material for important fluid properties, accuracy estimation and installation requirements for all commonly used flowmeters, guides to meter selection and accuracy, and coverage of linear/differential producers. Includes tabular and graphical representations of equations and extensive cross-referenced appendices.